Efeect of Age on Pulping Properties of Eucalyptus Hybrid (E. tereticornis) - Guha, S. R. D.; Singh, T. M.; Mathur, G. M. (Indian Forester, 1970)
The paper gives the details of work done on three years and six years old Eucalyptus hybrid (E. tereticornis of Mysore origin), grown in Kalanor Reserve Forest Plantation, in Haryana State. Woods were pulped by using different conditions for pulping and were bleached by multistage bleaching process. Wrapping, writing and printing paper made from pulps showed slight decrease in yields and strength properties with an increase in age of wood.